واقع المرأة السعودية المطلقة والصعوبات التي تواجهها - السقاف, أروى (جامعة الوادي - University of Eloued, 2021)
ملخص: تناولت هذه الدراسة واقع المرأة السعودية المطلقة وأبرز الصعوبات الاجتماعية والنفسية التي تواجهها، على اعتبار أن ظاهرة الطلاق لا تزال في تفاقم مستمر ونواتجها جسيمة خصوصاً على المرأة وأطفالها، وجاءت هذه الدراسة الوصفية بعد توظيف منهج دراسة الحالة التي استخدمت الباحثة فيه العينة العشوائية لاختيار مفردات عينة الدراسة من قوائم المطلقات المستفيدات من جمعية مودة الخيرية بمدينة الرياض والتي بلغ عددها 41 مطلقة، واعتمدت الباحثة في جمع بيانات الدراسة على سجلات المطلقات،والمقابلة المفتوحة، والاتصالات الهاتفية معهن، وتوصلت إلى نتائج منها ما يلي: -واقع المرأة السعودية المطلقة يشير إلى أمور منها انخفاض مستوى دخلها الشهري ومستوى تعليمها، كما تواجه المطلقة صعوبات اجتماعية كعدم التوافق الأسري والاجتماعي،وأما الصعوبات النفسية كان منها القلق، والاضطراب، والاغتراب. Abstract: This study tackles the reality of divorced Saudi women and the most prominent social and psychological difficulties they face, given that the divorce phenomenon is still in constant exacerbation and its outcomes are serious, especially for a woman and her children. This descriptive study came after employing the case study method in which the researcher used a random sample to choose the items of the study sample form the lists of divorced women who are benefited from the Mawaddah Charity Association in Riyadh, which numbered 41 divorced women. The researcher relied on collecting the study data on the records of divorced women, open interviews, and phone calls with them, and the results she reached include the following: The reality of a divorced Saudi woman indicates, among other things, a decrease of the level of her monthly income and the level of her education. The divorced woman also faces social difficulties such as family and social incompatibility. As for the psychological difficulties, they are such as anxiety, disturbance, and alienation.
مقال
Keywords: المرأة السعودية المطلقة- الطلاق- جمعية مودة النسائية الخيرية- الواقع- الصعوبات; divorced Saudi woman - divorce - Mawaddah Women's Charity Association- reality - difficulties